Laboratory diagnosis of blood of domestic cats with pancreatitis - Yu. F. Dereza; N. S. Kanivets (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
This paper presents the results of blood tests of domestic cats with chronic pancreatitis and at risk of pancreatic inflammation. The number of erythrocytes, leukocytes, platelets was analysed, as well as the value of haematocrit, serum transaminases, amylase, pancreatic lipase, glucose, total bilirubin, creatinine and urea. The examination revealed no specific symptoms of pancreatitis, although most of the animals showed signs of digestive disorders (exhaustion – 84 %, vomiting – 75 %, dehydration – 83 %, worsening or absence of appetite – 87.5 %, abdominal tenderness on palpation – 65 %). In the blood of sick cats (group one) and those at high risk of pancreatitis (group two), leukocytosis (Р < 0.001), erythrocytosis (Р < 0.01) and thrombocytopenia (Р < 0.001) were found, indicating a prolonged inflammatory process in the body against the background of blood thickening. Biochemical studies of blood serum in animals of the first group showed an increase in the activity of ALT and AST by 1.9 and 2.4 times (Р < 0.001) compared to the control group (clinically healthy animals), respectively. Similar changes were recorded in the animals of the second group, in which the activity of ALT and AST increased by more than 1.8 times (Р < 0.001) compared to clinically healthy animals. The serum total bilirubin (TBIL) content of cats of the first and second groups averaged 8.9 ± 064 and 10.9 ± 0.44 µmol/l, which was 1.6 and 2.0 times (Р < 0.001) higher than that of the control group, respectively. Such changes in hepatic parameters (ALT, AST, total bilirubin) indicate damage to the hepatobiliary system, which can have both acute and chronic course (cholangitis, lipidosis). Hyperglycaemia (Р < 0.001), increased amylase activity (Р < 0.001) and 2.2 and 1.6-fold increase in pancreatic lipase activity (Р < 0.001), respectively, were observed in cats with and at high risk of developing pancreatitis, which confirms the impaired functional state of the pancreas.